1996
DOI: 10.1111/j.1745-4506.1996.tb00314.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Knowledge of Food Safety Among Santa Clara County, California Restaurant Operators

Abstract: The idea for a food safety study within the restaurant population was brought to light by Joan Giampaoli, M.S., R.D. The study's query began with the intent to bridge the gap between those restaurant operators who know about food safety yet do not practice it and those who not only know food safety principles, but actually put them to use. It was brought to our attention that eliciting truthful responses to actual restaurant practices would be extremely difficult. Consequently, the query became “what differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 1 publication
0
24
0
Order By: Relevance
“…Cochran-Yantis, Belo, Giampaoli, McProud, Everly, and Gans (1996) reported that restaurant managers who had a favorable attitude toward food safety were more likely to score higher on inspection reports, while the converse holds true for those who do not have a favorable attitude. Hwang, Almanza, and Nelson (2001) extended this idea into school foodservice and found knowledge, training, and practice were all factors that led managers to be more favorable toward implementing Hazard Analysis Critical Control Point (HACCP), a food safety program.…”
Section: Experience and Food Safety Appreciation Pg 7 Of 27mentioning
confidence: 93%
See 1 more Smart Citation
“…Cochran-Yantis, Belo, Giampaoli, McProud, Everly, and Gans (1996) reported that restaurant managers who had a favorable attitude toward food safety were more likely to score higher on inspection reports, while the converse holds true for those who do not have a favorable attitude. Hwang, Almanza, and Nelson (2001) extended this idea into school foodservice and found knowledge, training, and practice were all factors that led managers to be more favorable toward implementing Hazard Analysis Critical Control Point (HACCP), a food safety program.…”
Section: Experience and Food Safety Appreciation Pg 7 Of 27mentioning
confidence: 93%
“…Attitudes toward food safety programs have been well researched (e.g., Cochran-Yantis, Belo, Giampaoli, McProud, Everly, & Gans, 1996;Hwang, Almanza, & Nelson, 2001;Roberts & Sneed, 2003). Cochran-Yantis, Belo, Giampaoli, McProud, Everly, and Gans (1996) reported that restaurant managers who had a favorable attitude toward food safety were more likely to score higher on inspection reports, while the converse holds true for those who do not have a favorable attitude.…”
Section: Experience and Food Safety Appreciation Pg 7 Of 27mentioning
confidence: 99%
“…Food safety training is associated with increased knowledge among foodservice operators (Lynch et al, 2003), and foodservice operators with better restaurant inspection scores have more knowledge and more favorable attitudes about food safety compared to operators with poor inspection scores (Cochran-Yantis et al, 1996). However, food safety knowledge is not always practiced by foodservice employees (Howes et al, 1996).…”
Section: Intervention Improves Restaurant Employees' Food Safety Compmentioning
confidence: 99%
“…Training increases knowledge (6) and improves attitudes for food safety (9,10), but rarely improves behavior (11)(12)(13)(14)(15). Food safety trainers, including RDs and DTRs, must identify strategies to minimize the gap between knowledge and action.…”
Section: Identifying Specific Beliefs To Target To Improve Restaurantmentioning
confidence: 99%
“…These beliefs can be targeted in interventions to improve compliance with safety guidelines. While past studies identified factors that influence food safety behaviors (9,(16)(17)(18)(19), no previous research explored the relative importance of such factors for multiple behaviors. …”
mentioning
confidence: 99%